Halvvejgård og Kongeengen – to nyundersøgte lokaliteter med hustomter fra senneolitikum og ældre bronzealder ved Vejen i Sydjylland.: Foreløbige betragtninger - Poulsen, Martin Egelund (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
In the central part of southern Jutland, two settlements with houses from the Late Neolithic and Early Bronze Age have recently been excavated in Vejen. At Halvvejgård and Kongeengen, respectively excavated in 2020 and 2022, seven two-aisled houses from the Late Neolithic and the earliest Bronze Age (c. 2300 – 1500 BC) were found along with ten three-aisled longhouses from the middle of the Early Bronze Age (c. 1500 – 1200 BC). Four of the twoaisled houses had sunken-floors, while two houses had wall trenches and represent a rarely excavated two-aisled house-type that sometimes features three-aisled elements. Nine three-aisled houses from the younger settlement had bole-walls, and three of these were of monumental size, measuring 39 – 45 × 8 m. Observations in some of the postholes clearly support the interpretation as bole-walls. Two of these houses have remarkably early radiocarbon dates, which is relevant in the discussion of the transition between the two- and three-aisled building tradition. The settlements at Halvvejgård and Kongeengen represent new important additions to earlier excavated Late Neolithic and Early Bronze Age settlements in the local area and the region of southern Jutland as well.